On 'What Is Maoism?': Some Comments - CHATTOPADHYAY, PARESH (Economic and political weekly, 2010)
In this rejoinder to Bernard D'Mello's "What Is Maoism?" (EPW, 21 November 2009), Paresh Chattopadhyay argues, among other things, that (1) the reader is not given the opportunity to verify whether the author's interpretations tally with the original texts of Marx, Lenin and Mao because he does not quote from the original texts; (2) the author and Paul Sweezy are wrong in particular interpretations of Marx and Engels; (3) Lenin misinterpreted Marx on socialism and was responsible for the degeneration of the Russian Revolution; (4) Mao was an ideological Stalinist; and (5) the category Cultural Revolution is alien to Marx.